On Matrix Representations of Octonions - Ali, Hassan. S. (Scientific Journal of University of Benghazi, 2021)
The real Quaternions over is an associative division algebra.They can be linearly represented by 4×4 real matrices. The real Octonions over is a non –associative division algebra. They can't be represented linearly by matrices as in the case of . The point of this paper is to represent Octonions linearly by ordered pairs of two 4×4 matrices.